2017
DOI: 10.1140/epjc/s10052-017-5050-z
|View full text |Cite
|
Sign up to set email alerts
|

Studying the intervention of an unusual term in f(T) gravity via the Noether symmetry approach

Abstract: As has been done before, we study an unknown coupling function, i.e. F(ϕ), together with a function of torsion and also curvature, i.e. f (T ) and f (R), generally depending upon a scalar field. In the f (R) case, it comes from quantum correlations and other sources. Now, what if beside this term in f (T ) gravity context, we enhance the action through another term which depends upon both scalar field and its derivatives? In this paper, we have added such an unprecedented term in the generic common action of f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Although numerous models have been proposed to explain this phenomenon, this transition still has not been explained consistently Refs. [11][12][13][14][15][16][17][18][19][20]. Without understanding this critical transition, it seems to be unlikely to proceed toward a comprehensive theory of cosmology.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous models have been proposed to explain this phenomenon, this transition still has not been explained consistently Refs. [11][12][13][14][15][16][17][18][19][20]. Without understanding this critical transition, it seems to be unlikely to proceed toward a comprehensive theory of cosmology.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 6 This figure demonstrates the plot of f (R) for four options of interest (1-Pure electromagnetic case (blue color); 2-Pure matter case (green color); 3-Both electromagnetic and matter cases (red color); 4-Vacuum case (orange color)) at curvature interval [13,35] of their amounts, satisfy this relation: em 9 > m + em 10 > vacuum 11 > m 12 (see Figs. 6,7,8).…”
Section: The Variable Jerk Case J = Q(t) (N = 3)mentioning
confidence: 82%
“…This mysterious candidate being incompatible with strong energy condition is dubbed as dark energy. This cosmic behavior can also be explained either by modifying matter part ( f (R) gravity, f (T ) gravity, f (T ) gravity with unusual term [9], scalartensor theories [10], etc.) or by modifying geometric part (chaplygin gas [11], quintessence [12], phantom [13], quintom [14], etc.)…”
Section: Introductionmentioning
confidence: 99%
“…As is observed, in the special case m = 1 (FRW), both are equal: n 1 = n 2 = 1/3 . It is important to mention that if one wants to examine FRW-case, then he must take k 1 = k 2 / √ 2 in (25). In this stage, we encounter a bifurcation in equations due to n , and therefore two classes are separated by it.…”
Section: Nother Symmetry Approach and Csss-trickmentioning
confidence: 99%
“…In this stage, we encounter a bifurcation in equations due to n , and therefore two classes are separated by it. Indeed, the suitable solutions obtained by Noether symmetry approach, do not allow to have a four-potential of the form (25), hence, it is readily observed that (25) must be split into two independent cases:…”
Section: Nother Symmetry Approach and Csss-trickmentioning
confidence: 99%